(3HZjI GdadGMjf ddCTLGQ GdeKeQI hGdQjGMjfs - (3YHGS Hf Ydj Hf OGhO Hf GdeXaQ jhSa GdQShdj GdZSGfj, Gdedc GdCaVd , J (B778 (3g` s
(3ChdgG (B:s
(3hHYOEfi deG JhdGfi Gddg YR hLd HZjI YfGjJgHJCdja cJGH Jchf LhGgQ eYQaJg s
(3BNQgG (B:s
(3fHPI ai PcQ GdCbGdje GdSHYI, heG jJYdb HgG ef GdadGMI hJfJgi HhbaI bde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B262 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa (B- (3U (B185 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK HGSJGfHhd (B(2432) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdRQGYI h GdCYTGHs